PROTECTION OF ADAPTATION ART EXPRESSION IN FILM COPYRIGHTS ACCORDING TO LAW NUMBER 28 OF 2014 CONCERNING COPYRIGHTS - Efridani Lubis; Sinta Elviyanti (JURNAL HUKUM DE'RECHTSSTAAT, 2022)
Adaptive film is one of creative works that protected under Law No. 28 Year 2014 of Copyright. Along with the process however, adaptive film creators are often facing grey area that fall into infringement others’ creation at the end. Most cases were the creators did not publish, whatsoever, the name of original creators which also considered as moral right. Although it seems an infringement at a glance, there needs a depth discussion further regarding substantial part of such creation that also contains creativity that also acknowledged and protected. Based on this consideration, this study focus on identifying adaptation process that comply with related regulations in Indonesia. The study used normative-legal approach based on study documents with regulations as primary legal resources. The analysis conducted through reviewing legal theories, concepts, and principles. The result of study shows that substantial-creative works that differ from its original work could be protected according to copyright law. While the infringement of original works could also process according to Law No. 11 Year 2008 of Electronic Information and Transaction as revised with Law No. 19 Year 2016.